Tratamiento y nuevas alternativas de control de las cestodosis en la gallina domestica. Parte I - Ruiz, C.R.=700 1 Larramendy, R.; Szczypel, B.; Gonzalez, M.
(Es, En)
Ilus., ref.
Keywords: AVES DE CORRAL; CESTODA; HUESPEDES INTERMEDIARIOS; NICLOSAMIDA; CUBA; METARHIZIUM ANISOPLIAE; REVISTA CUBANA DE CIENCIA AVICOLA